USE OF AERIAL METHODS IN LANDSCAPE STUDIES - Viktorov,S. V. (1969)
The collection of articles covers a wide range of problems: The use of aerial methods in the tundra, taiga, stepps, and sandy deserts; the possibilities of aerial methods for the study of regional characteristics of landscapes; and the applications of aerial photography for large-scale mapping. (Author) Trans. of unidentified Russian language mono. pub. by Academy of Sciences, 1959.